Assessment of antibody levels in a population vaccinated with Sputnik V - Diego Gonzalez; Federico Fortuna; Analy F. Fritzler; Juan J. Jamardo; Eliana Duarte; Carolina Ibar; Dario G. Jacobsen; Maria E. Estevez; J Aguirre; Belky B. Garzón; Ruben Absi; Esteban M. Repetto; et al. (Russian Open Medical Journal)
Objectives — The objective of our study was to assess humoral response in a population of health workers after vaccination with the first and second doses of Sputnik V. Methods — SARS-CoV-2 total antibodies (IgG and IgM) were measured, using the Centaur XPT autoanalyzer, Siemens®, in 530 serum samples taken from health workers in Buenos Aires vaccinated with Sputnik V. Results — After 21 days of the first dose application, 10 individuals (1.9%) presented antibody levels <1.0 (non-reactive), while 520 subjects (98.1%) responded with antibody values >1.0 (reactive). The results, obtained 21 days after the second dose, show that only 2 individuals (0.38%) had antibody levels <1.0 (non-reactive) and 528 (99.6%) responded with antibody values >1.0 (reactive). Conclusion — This study results implied that two doses of Sputnik V vaccine generated a proper antibody response in virtually the entire studied population.